Key technologies and implementation methods of endogenous safety and security cloud data center based on mimic architecture - Fan ZHANG; Guangwei XIE; Wei GUO; Hongchao HU; Ruyun ZHANG; Wenyan LIU (Dianxin kexue)
Cloud data center is the representative of the new generation of information infrastructure, and its security has become the focus of attention in recent years, which is of great significance.Based on the analysis of the current cloud security situation, the security architecture, key technologies, and implementation methods of the cloud data center through the emerging concept of endogenous security were explored, hoping to use the mimic structure to solve the endogenous safety and security problems such as vulnerabilities and backdoors that were difficult to deal with by the existing means.Moreover, the endogenous security architecture of cloud data centers and related key technologies were proposed, with the mode and trend of mimic transformation.In the future, endogenous safety and security cloud data centers will provide practical solutions for the construction of a new generation of information infrastructure, which may accelerate the technology application and promotion of the cloud service model.